Effects of a drill diameter on the temperature rise in a bone during implant site preparation under clinical conditions. (October 2016) - Bogovič, Valerija; Svete, Andrej; Bajsić, Ivan
Heat, generated during the drilling of a dental implant site preparation, leads to a temperature rise and consequently to a thermal injury of the bone tissue surrounding the implant site, which can cause the subsequent implant failure. In this article, we present new findings related to the temperature rise during implant site drilling under real conditions on a bovine rib bone specimen. The experiments were designed with the help of a full-factorial design in randomized complete blocks, where the main effects of the drill diameter in combination with the drilling force and the drilling speed, and their interactions, on the temperature rise were determined. The temperature rise in the bone under real conditions was measured as the implant site was being prepared by a dentist using intermittent, graduated drilling and external irrigation. Results show that the drill diameter has statistically significant effect, independent of the drilling procedure used. Among the examined drilling parameters, the drill diameter has the greatest effect, where an increase in the drill diameter first causes a decrease in the temperature rise and further increase in the drill diameter causes its increase. During the continuous and one-step drilling, the temperatures of the bones were up to 40.5 °C and during the drilling under actual conditions up to 30.11 °C.